Characterization of KRAS Mutational Regression in Oligometastatic Patients - Ottaiano, Alessandro; de Vera d’Aragona, Roberta Penta; Trotta, Anna Maria; Santorsola, Mariachiara; Napolitano, Maria; Scognamiglio, Giosuè; Tatangelo, Fabiana; Grieco, Paolo; Zappavigna, Silvia; Granata, Vincenza; Perri, Francesco; Luce, Amalia; et al. (Frontiers in Immunology, 2022)
Background. We previously reported rare regressive genetic trajectories of KRAS pathogenic mutations as specific hallmark of the genuine oligo-metastatic status in colorectal cancer (CRC). Methods. Survival and prognostic impact of disease extent in 140 metastatic CRC patients was evaluated through the Kaplan-Meyer curves and the Log-Rank test. KRAS mutations were assessed through the Illumina NovaSeq 6000 platform and TruSight™Oncology 500 kit. HLA typing was carried out by PCR sequence-specific oligonucleotides. Lymphocyte densities in tumours were expressed as cells per mm2. NKs isolated and CD8+ from NK-depleted PBMC were characterized through flow-cytometry. CD107a externalization was evaluated as NKs/CD8 cytotoxicity toward human colon cancer cells HT29, SW620, HCT116, LS174T carrying different KRAS mutations. Results. The oligo-metastatic status was a strong and independent variable for survival (HR: 0.08 vs poly-metastatic disease; 95% CI: 0.02-0.26; P<0.001). Eighteen oligo-metastatic patients were selected. Twelve were alive at last follow-up, 9 were characterized. Genetic regression of KRAS was observed in 3 patients: PAT2, PAT5 and PAT8. PAT2 and PAT5 presented the highest values of GrzB+ lymphocytes into tumour cores of the metastases (120+11.2 and 132+12.2 cells/mm2, respectively). Six out of 9 patients (67%), including PAT2 and PAT5, expressed HLA-C7. Two patients (PAT2 and PAT5) presented high CD3+/CD8+-dependent cytotoxicity against HLA-C7+ SW620 cells (p.G12V mutated cells) which was consistent with their observed mutational regression (p.G12V/p.G13D in primary→p.G13D in metastatic tumour). Conclusions. We provide evidence that CD3+/CD8+ lymphocytes from oligo-metastatic CRC patients display differential cytotoxicity against human colon cancer cells carrying KRAS mutations. This could provide an interesting basis for monitoring oligo-metastatic disease and developing future adoptive immunotherapies.